Mapping the Discourse of Gender Subordination in the Art World in Indonesia - Wirajati, Yohanes De Britto (Bina Nusantara University, 2024)
Instead of hastily trying to throw out a discourse that rarely or has never appeared in related discussions, what then becomes the breath of the analysis in this scientific article is an effort to mapping the position of women's gender subordination and the representation of women artists discourses in the dialogue of a special scope, namely Indonesian art world. The analysis was carried out using three theoretical concepts, namely subordination, symbolic violence and representation in the art world in Indonesia. By conducting a literature study on literature and art events, the results of this scientific research show that: (1) Collective awareness is believed to support the articulation of resistance to gender inequality; (2) This awareness extends to the involvement of male artists as well, but there are other articulation practices that are more reflective in nature, meaning the construction of the gender identity of the female artist; and (3) The condition of gender inequality is also voiced in-depth reflections aimed at erasing the gender dichotomy caused by stereotypes.